Engaging the Modern Consumer: A Review of Customer Engagement in Recent Years - Vu, Hanh T. My (Archives of Business Research, 2025)
In a market characterized by consumers who are more demanding and actively involved, both academics and practitioners have shown growing interest in the concept of customer engagement (CE). Although the significance of CE is well acknowledged, the research in this field is still considerably disjointed, with several definitions and conceptualizations found in the existing literature, potentially resulting in more divergence in future studies. This report provides a systematic review of the existing research on CE from 2013 to 2022. This review covers the main conceptualizations, manifestations, measurements, and nomological network of the construct. From the emerging themes, the report offers scholars with conceptual, methodological, and topical direction in CE research.